2011
DOI: 10.1128/jcm.01338-10
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Deletion-Based Subtyping System for the Manila Family of Mycobacterium tuberculosis

Abstract: The Manila family of Mycobacterium tuberculosis is a group of clonal isolates seen throughout the Pacific Basin. Commonly used rapid molecular typing methods often leave large groups of Manila family isolates clustered together. Here we describe a simple deletion-based PCR method that improves the discrimination for Manila family isolates, with or without the use of mycobacterial interspersed repetitive-unit-variable-number tandem-repeat (MIRU-VNTR) classification, and that is both rapid and affordable. Twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…A few spoligotyping studies in other island countries, such as in Kiribati 35 and Papua New Guinea 36 , 37 , revealed the rarity of the EAI isolates. The rare EAI isolates, however, usually belonged to EAI2_MNL, which was also reported from Hawaii and Guam 38 . Thus, L1.2.1.1 may associate with Austronesians either due to the founder effect or co-evolution.…”
Section: Discussionsupporting
confidence: 52%
“…A few spoligotyping studies in other island countries, such as in Kiribati 35 and Papua New Guinea 36 , 37 , revealed the rarity of the EAI isolates. The rare EAI isolates, however, usually belonged to EAI2_MNL, which was also reported from Hawaii and Guam 38 . Thus, L1.2.1.1 may associate with Austronesians either due to the founder effect or co-evolution.…”
Section: Discussionsupporting
confidence: 52%
“…Regions amplified by PCR were sequenced to confirm the reaction. A detailed explanation of this methodology has been described [9] .…”
Section: Methodsmentioning
confidence: 99%
“…Classical genotyping techniques such as MIRU-VNTR and spoligotyping also have lower discriminatory power compared to WGS (Phelan et al 2019;Jamieson et al 2014), especially for the Manila strain that has been shown to have very low genetic variability (Douglas et al 2003;Frink et al 2011). It is also possible that the lower discriminatory power of these genotyping tools…”
Section: Discussionmentioning
confidence: 99%